Cover crop management in a Sauvignon blanc/Ramsey vineyard in the semiarid Olifants River Valley, South Africa. 1. Effect of management practices on selected grass and broadleaf species - Fourie, J.C.; Louw, P.J.E.; Agenbag, G.A. (South African Journal of Enology and Viticulture, 2017)
This trial was conducted over a period of ten years on a sandy soil in a Sauvignon blanc/Ramsey vineyard in Lutzville (31°35’S, 18°52’E), situated in the semi-arid Olifants River Valley of the Western Cape. Twenty-three treatments were applied. Eight cover crop species that received the same amount of fertilizer were controlled chemically at the end of August or at the end of November. Two treatments were also applied in which Avena sativa L. v. Saia (‘Saia’ oats) and Vicia dasycarpa Ten. (grazing vetch) were controlled mechanically during bud break. In addition to these eighteen treatments, two fertiliser application rates were applied to ‘Saia’ oats and grazing vetch. A mechanically cultivated control in which no cover crop was sown was included in the trial. Secale cereale L v. Henog and Ornithopus sativus L. v. Emena produced, on average, the highest amount of dry matter at the end of August (3.29 t/ha and 3.06 t/ha, respectively) after receiving on average 278 mm of water, of which 172 mm was supplied by means of a micro-sprinkler irrigation system. The average dry matter produced by Medicago truncatula Gaertn. v. Paraggio and ‘Saia’ oats at the end of August was not significantly lower than that of the firstmentioned two species. Under conditions of this experiment, it seemed that P and K at a concentration of 10 mg/kg and 78 mg/kg, respectively, in the top 300 mm soil layer supplied the needs of grazing vetch. Saia oats performed poorly unless 30 kg P, 30 kg K and 42 kg N were applied during establishment and the early growing phase. All the species, except M. truncatula Gaertn v. Parabinga, produced additional fibre from September to the end of November following a dry winter (rain and irrigation totaling 201 mm), while none produced additional fibre if the water supply was luxurious up to the end of August (rain and irrigation totaling 364 mm). The cover crops did not produce enough seeds to re-establish successfully over a period of five years. It will, however, be possible to reduce the seeding density of grazing vetch (40% after two seasons) and the two M. truncatula varieties (20% after five seasons) if the species were left to ripen their seeds.